Influence Of Formation Conditions, Subsequent Annealing and Ion Irradiation on the Properties of Nanostructured Coatings Based on Amorphous Carbon with Gold, Silver and Nitrogen Additives - Kolpakov, Aleksandr; Poplavsky, Aleksandr; Yapryntsev, Maksim; Novikov, Vseslav; Manokhin, Sergey; Goncharov, Igor; Galkina, Marina; Beresnev, Vyacheslav (East European Journal of Physics, 2021)
Nanostructured coatings based on amorphous carbon and carbon-doped with gold, silver, and nitrogen were obtained by the pulsed vacuum-arc method. Carbon coatings have been annealed in a vacuum as well as treated with argon ions. The alloying of carbon coatings with elements that do not form chemical bonds with the carbon matrix (Ag, Au) leads to the formation of gold or silver nanocrystallites with sizes of 2 ‑ 20 nm in the matrix of amorphous carbon, whose density depends on the concentration of the doping element. Annealing of silver-doped carbon coatings leads to the formation of islands on the surface with the size of the order of micrometers. This is due to the silver diffusion and coalescence of small islands into larger ones. The HRTEM method discovered the effect of twinning in carbon nanocrystallites after vacuum annealing as well as silver and gold in the initial state (the formation of single-crystal regions with an altered orientation of the crystal structure) in the amorphous carbon matrix. Analysis of Raman spectra of pure carbon coating and silver-doped showed that the addition of silver leads to a decrease in sp3-phase in the carbon matrix. This effect is particularly evident in the nature of changes in the spectra after vacuum annealing at 600 ºC. The addition of nitrogen in the carbon coating leads to an increase in the sp2 ‑ phase fraction, and additional annealing leads to a significant increase in the D - peak intensity and formation of clusters of the order of 5 ‑ 15 nm, which are not localized but fill the entire space. Analysis of the coating a-C: Au irradiation with argon ions shows that the number of nanopitches decreased after ion irradiation, simultaneously decreased surface roughness degree, besides, decreased electrical conductivity of the coating as a result of decreased gold content. It was found that the conditions of nanostructured coatings and their subsequent processing allow controlling the properties of nanocoatings (structure, size of nanoparticles, surface topography, and electrical conductivity).